Successful human long-term application of in situ bone tissue engineering - Horch, Raymund; Kneser, Ulrich (Journal of cellular and molecular medicine, 2014)
Tissue Engineering (TE) and Regenerative Medicine (RM) have gained much popularity because of the tremendous prospects for the care of patients with tissue and organ defects. To overcome the common problem of donor-site morbidity of standard autologous bone grafts, we successfully combined tissue engineering techniques for the first time with the arteriovenous loop model to generate vascularized large bone grafts. We present two cases of large bone defects after debridement of an osteomyelitis. One of the defects was localized in the radius and one in the tibia. For osseus reconstruction, arteriovenous loops were created as vascular axis, which were placed in the bony defects. In case 1, the bone generation was achieved using cancellous bone from the iliac crest and fibrin glue and in case 2 using a clinically approved β-tricalciumphosphate/hydroxyapatite (HA), fibrin glue and directly auto-transplanted bone marrow aspirate from the iliac crest. The following post-operative courses were uneventful. The final examinations took place after 36 and 72 months after the initial operations. Computer tomogrphy (CT), membrane resonance imaging (MRI) and doppler ultrasound revealed patent arterio-venous (AV) loops in the bone grafts as well as completely healed bone defects. The patients were pain-free with normal ranges of motion. This is the first study demonstrating successfully axially vascularized in situ tissue engineered bone generation in large bone defects in a clinical scenario using the arteriovenous loop model without creation of a significant donor-site defect utilizing TE and RM techniques in human patients with long-term stability.
Gesehen am 11.08.2020